Inhibitory Effect of N-Hexane Fraction of Cherry Parasite (Dendrophthoe pentandra L.) on Alpha Glucosidase - Sadakata Sinulingga; Putriana Fuji Safitri; Subandrate (HM Publisher, 2022)
Background. Cherry parasite (Dendrophthoe pentandra L.) is a semi-parasitic plant that takes food from host body, so that phytochemical same as host plant. These phytochemicals have effect to inhibiting the action of the enzyme alpha glucosidase, such as flavonoids, saponins, tannins, alkaloids, and terpenoids/steroids. The aim of this study is to find out the effect of the cherry parasite to inhibiting the enzyme alpha glucosidase. Methods. This is an in vitro experimental study. Cherry parasite was fractionated with n-hexane and reacted by enzyme. Acarbose used as a positive control. The inhibitory effect on the alpha glucosidase was determined from the IC50 value by measuring the absorbance of p-nitrophenol using spectrophotometry as a result of the reaction of the enzyme. Screening phytochemical to determine the phytochemical of n-hexane fraction. This research was conducted at the Laboratory of Biochemistry and Medical Chemistry, Faculty of Medicine, Universitas Sriwijaya, Palembang. Results. The yield of n-hexane fraction was 7%. Phytochemical test showed that the sample contain flavonoids and terpenoids. IC50 value of n-hexane fraction was 106,333 ppm and categorized not active. Conclusion. The n-hexane fraction of cherry parasite contains flavonoids and terpenoids that considered not active to inhibiting the action of the enzyme alpha glucosidase.